2020
DOI: 10.1101/2020.02.19.953034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxidative Modifications of Parkin Underlie its Selective Neuroprotection in Adult Human Brain

Abstract: The mechanisms by which Parkinson disease-linked parkin confers neuroprotection of human dopamine cells remain elusive. We hypothesized that its cysteines mediate multiple anti-oxidant effects in the midbrain. By studying >60 control specimens, we found that in adult human brainbut not in skeletal muscle-parkin is mostly aggregated and insoluble due to oxidative modifications, such as at C253. In vitro, parkin's oxidation directly reduces hydrogen peroxide (H2O2) to water. In parkin-deficient human brain, H2O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In addition, Meng et al described that Parkin can be sulfonated in an in vitro Parkinson's model, leading to protein aggregation, and possibly contributing to the formation of Lewy's bodies in Parkinson's [ 298 ]. However, in a recent article (at preprint stage at the point of writing this review), Tokarew et al highlighted the importance of Parkin's own oxidation in neuroprotection [ 299 ]. Previously, Vandiver et al showed that Parkin can also undergo sulfhydration, enhancing its catalytic activity and its protective function [ 300 ].…”
Section: Autophagy and Redoxtasis Crosstalkmentioning
confidence: 99%
“…In addition, Meng et al described that Parkin can be sulfonated in an in vitro Parkinson's model, leading to protein aggregation, and possibly contributing to the formation of Lewy's bodies in Parkinson's [ 298 ]. However, in a recent article (at preprint stage at the point of writing this review), Tokarew et al highlighted the importance of Parkin's own oxidation in neuroprotection [ 299 ]. Previously, Vandiver et al showed that Parkin can also undergo sulfhydration, enhancing its catalytic activity and its protective function [ 300 ].…”
Section: Autophagy and Redoxtasis Crosstalkmentioning
confidence: 99%